Auditors’ Opinions and Tax Aggressiveness in Brazilian Companies - Lopo Martinez, Antonio; dos Santos, Fernando Ferreira; Carvalho Júnior, César Valentim de Oliveira; Bastos, Sergio Augusto Pereira; Rodrigues, Josiel Caldas (RC&C: Revista de Contabilidade e Controladoria, 2025)
This study delves into the intricate relationship between independent auditor opinions and corporate tax aggressiveness. We investigate whether the characteristics of auditor opinions, such as the presence of caveats, length, readability, and verbal tone, signal a company’s tendency to engage in aggressive tax practices. Utilizing a quantitative approach, we employed a multiple linear regression model on a dataset of 1,271 observations from companies listed on the B3 stock exchange between 2017 and 2022. Tax aggressiveness was measured using established proxies like book-tax differences (BTD), effective tax rate (ETR), and tax rate on value added (TTVA). Our findings reveal a lack of significant correlation between the informational content of auditor opinions and corporate tax aggressiveness. Contrary to expectations, characteristics such as caveats, length, readability, and verbal tone did not significantly signal corporate tax strategies. This suggests that while auditor opinions are vital for financial reporting and corporate governance, their ability to indicate tax practices might be limited or indirect. These insights add to the discourse on corporate governance and tax compliance, promoting transparent and equitable business practices. Further research is needed to identify other factors that may influence tax aggressiveness and to better understand the dynamics between auditors and corporate tax strategies.